2022
DOI: 10.1007/s00422-022-00952-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between an exact and a heuristic neural mass model with second-order synapses

Abstract: Neural mass models (NMMs) are designed to reproduce the collective dynamics of neuronal populations. A common framework for NMMs assumes heuristically that the output firing rate of a neural population can be described by a static nonlinear transfer function (NMM1). However, a recent exact mean-field theory for quadratic integrate-and-fire (QIF) neurons challenges this view by showing that the mean firing rate is not a static function of the neuronal state but follows two coupled nonlinear differential equatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Overall, the large-scale brain model with NG-NMMs displays a mechanism towards the onset of irregular states analogous to the Jansen case, despite the different nature of the two models [89]. For instance, we did not include synaptic dynamics in Eq (36), i.e., neurons receive instantaneous delta-like pulses.…”
Section: Spatiotemporal Chaos In a Large-scale Brain Model With Next ...mentioning
confidence: 99%
“…Overall, the large-scale brain model with NG-NMMs displays a mechanism towards the onset of irregular states analogous to the Jansen case, despite the different nature of the two models [89]. For instance, we did not include synaptic dynamics in Eq (36), i.e., neurons receive instantaneous delta-like pulses.…”
Section: Spatiotemporal Chaos In a Large-scale Brain Model With Next ...mentioning
confidence: 99%
“…Overall, the large-scale brain model with NG-NMMs displays a mechanism towards the onset of irregular states analogous to the Jansen case, despite the different nature of the two models [85]. For instance, we did not include synaptic dynamics in Eq (36), i.e., neurons receive instantaneous delta-like pulses.…”
Section: Spatiotemporal Chaos In a Large-scale Brain Model With Next ...mentioning
confidence: 99%
“…Neural entrainment becomes weaker as network size and number of synapses decrease (figure S7). Entrainment relies on slight shifts in spike timings at single cell level that are amplified by network effects, such as number of neurons and synaptic connections affected by the weak exogenous electric field [5,32,73].…”
Section: Discussionmentioning
confidence: 99%
“…However, an isolated single PY cannot account for all tACS effects. To study the network-level effect of tACS, many modeling studies have utilized mean-field/neural mass models [5,[32][33][34][35], as well as spiking neuronal networks of single-compartment point neurons [15,36,37]. These models demonstrated that an applied oscillating electric field causes network resonance in neuronal populations [5,[32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation